EFFECTS OF VARIATION IN UMBILICAL ARTERY FLOW ON FOETAL MIDDLE CEREBRAL ARTERY FLOW IN HYPERTENSIVE PREGNANCIES - Jerome Borges, Kevin Joseph; Hassan, Nuzhat; Hussain, Rubina; Akhtar, M. Tameem (Pakistan Journal of Physiology, 2013)
Introduction: Cerebral vasodilation occurs in conditions of hypovolemia and cerebral hypoxia in adults. This effect is also found in foetuses. In gestational hypertension, blood flow to the foetus is compromised creating a situation somewhat similar to hypovolemia and cerebral hypoxia. Doppler ultrasound indices namely Resistive Index (RI) Pulsatility Index (PI) and Systolic-Diastolic Ratio (S/D)are useful tools in picking these changes in blood flow. The aim of this study was to see the effects of alterations in umbilical artery flow on foetal middle cerebral arterial flow with Doppler ultrasound parameter. Material and Methods: Ninety pregnant women with pregnancy-induced hypertension were selected with gestational age >35 weeks. Doppler ultrasound examination were carried out to record Pulsatility Index (PI), Resistive Index (RI), and Systolic-Diastolic Ratio (S/D) of Umbilical artery (UA) and Foetal Middle Cerebral Artery (MCA). Pearson’s correlation was determined between UA and MCA PI, RI and SD. Results: A non-significant (p=0.067) negligible negative correlation (r= -0.194) was seen between UA PI and MCA PI. A significant (p=0.000) very strong negative correlation (r= -0.754) was present between the UA RI and MCA RI. A significant (p=0.002) moderate negative correlation (r= -0.328) was observed between UA SD and MCA SD. Conclusion: A significant negative correlation was observed between the resistive indices and SD ratios of umbilical and middle cerebral arteries. No significant correlation was found between the pulsatility indices of the two arteries. Pak J Physiol 2013;9(2):15–8